Negotiating modernism in Cape Town: 1918-1948 : an investigation into the introduction, contestation, negotiation and adaptation of modernism in the architecture of Cape Town - Van Graan, André (School of Architecture, Planning and Geomatics, 2015)
In the early twentieth century modernism radically changed the world, affecting all aspects of life. Twentieth century modernism incorporated new inventions that changed the modes of travel, it restructured methods of production and the way in which people lived, worked and played. This radical change was to be reflected in all sectors, and was particularly manifested physically in architecture. Modernism demanded a radical shift from an architecture that had been slowly evolving from nineteenth century eclecticism, overlaid with reactionary concerns for the overwhelming impact of industrialisation on society and on the built fabric of cities. It sought to identify new ways of dealing with these issues and finding new methods of spatial production and ultimately creating a new means of architectural aesthetic expression that came to be referred to as the Modern Movement. The response to the radical change implied in modernism resulted in a process of negation and contestation, leading through negotiation to a mediated compromise before an ultimate acceptance.